Patient-Reported Outcomes Measurement Information System (PROMIS) Assessment of Non-Motor Features in Deep Brain Stimulation Candidates: Relationship to the Beck Depression and Anxiety Inventories. (2nd November 2020) - Loring, David W; Block, Cady; Staikova, Ekaterina; Miocinovic, Svjetlana
Abstract: Objective: To compare Patient-Reported Outcomes Measurement Information System (PROMIS) measures of depression and anxiety to the Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), and explore patterns of selected PROMIS measures in patients undergoing evaluation for Deep Brain Stimulation (DBS). Method: BDI-II, BAI, and seven PROMIS measures were administered to 163 DBS candidates with diagnoses of Parkinson Disease (PD, n  = 102), Essential Tremor (ET, n  = 45), or Dystonia ( n  = 16). Results: Elevated PROMIS Depression using BDI-II Crosswalk equivalents predicted elevated BDI-II with 63% sensitivity and 94% specificity. On other PROMIS measures, 69 patients (42%) reported low Physical Function (T ≤ 40) with Pain Interference being the next most frequent abnormal score ( n  = 51, 31%). Group differences were present for PROMIS Physical Function, Sleep Disturbance, and Pain. Conclusions: These preliminary findings provide initial support for PROMIS Depression to assess mood disturbance in DBS candidates, and characterize other PROMIS measures in DBS candidates including group differences reflecting disease specific contribution to Quality of Life.